The effect of compulsory schooling on health: Evidence from biomarkers - Hendrik Jürges; Eberhard Kruk; Steffen Reinhold (Center for Economic Studies and ifo Institute (CESifo), 2010)
Using data from the Health Survey for England and the English Longitudinal Study on Ageing, we estimate the causal effect of schooling on health. Identification comes from two nation wide increases in British compulsory school leaving age in 1947 and 1973, respectively. Our study complements earlier studies exploiting compulsory schooling laws as source of exogenous variation in schooling by using biomarkers as measures of health outcomes in addition to self-reported measures. We find a strong positive correlation between education and health, both self-rated and measured by blood fibrinogen and C-reactive protein levels. However, we find ambiguous causal effects of schooling on women's self-rated health and insignificant causal effects of schooling on men's self-rated health and biomarker levels in both sexes.
Keywords: I12; I20; 330; health; compulsory schooling; biomarkers; regression discontinuity; Schulrecht; Bildungsverhalten; Gesundheit; England